Oliver Twist - Dickens, Charles (Saga Egmont, 2017)
Oliver Twist by Charles Dickens is a classic novel that tells the story of an orphan boy who is forced to live a life of crime. The novel is set in the early 19th century in London and follows Oliver as he tries to escape from a life of poverty and violence. The novel is considered to be one of Dickens' best works and is still popular today.